Determinants of dihydroartemisinin-piperaquine treatment failure in Plasmodium falciparum malaria in Cambodia, Thailand, and Vietnam: a prospective clinical, pharmacological, and genetic study. Issue 9 (September 2019) - van der Pluijm, Rob W; Imwong, Mallika; Chau, Nguyen Hoang; Hoa, Nhu Thi; Thuy-Nhien, Nguyen Thanh; Thanh, Ngo Viet; Jittamala, Podjanee; Hanboonkunupakarn, Borimas; Chutasmit, Kitipumi; Saelow, Chalermpon; Runjarern, Ratchadaporn; Kaewmok, Weerayuth; et al.
Summary: Background: The emergence and spread of resistance in Plasmodium falciparum malaria to artemisinin combination therapies in the Greater Mekong subregion poses a major threat to malaria control and elimination. The current study is part of a multi-country, open-label, randomised clinical trial (TRACII, 2015–18) evaluating the efficacy, safety, and tolerability of triple artemisinin combination therapies. A very high rate of treatment failure after treatment with dihydroartemisinin-piperaquine was observed in Thailand, Cambodia, and Vietnam. The immediate public health importance of our findings prompted us to report the efficacy data on dihydroartemisinin-piperaquine and its determinants ahead of the results of the overall trial, which will be published later this year. Methods: Patients aged between 2 and 65 years presenting with uncomplicated P falciparum or mixed species malaria at seven sites in Thailand, Cambodia, and Vietnam were randomly assigned to receive dihydroartemisinin-piperaquine with or without mefloquine, as part of the TRACII trial. The primary outcome was the PCR-corrected efficacy at day 42. Next-generation sequencing was used to assess the prevalence of molecular markers associated with artemisinin resistance ( kelch13 mutations, in particular Cys580Tyr) and piperaquine resistance ( plasmepsin-2 and plasmepsin-3 amplifications and crt mutations). This study is registered with ClinicalTrials.gov, number NCT02453308 . Findings: Between Sept 28, 2015, and Jan 18, 2018, 539 patients with acute P falciparum malaria were screened for eligibility, 292 were enrolled, and 140 received dihydroartemisinin-piperaquine. The overall Kaplan-Meier estimate of PCR-corrected efficacy of dihydroartemisinin-piperaquine at day 42 was 50·0% (95% CI 41·1–58·3). PCR-corrected efficacies for individual sites were 12·7% (2·2–33·0) in northeastern Thailand, 38·2% (15·9–60·5) in western Cambodia, 73·4% (57·0–84·3) in Ratanakiri (northeastern Cambodia), and 47·1% (33·5–59·6) in Binh Phuoc (southwestern Vietnam). Treatment failure was associated independently with plasmepsin2/3 amplification status and four mutations in the crt gene (Thr93Ser, His97Tyr, Phe145Ile, and Ile218Phe). Compared with the results of our previous TRACI trial in 2011–13, the prevalence of molecular markers of artemisinin resistance ( kelch13 Cys580Tyr mutations) and piperaquine resistance ( plasmepsin2/3 amplifications and crt mutations) has increased substantially in the Greater Mekong subregion in the past decade. Interpretation: Dihydroartemisinin-piperaquine is not treating malaria effectively across the eastern Greater Mekong subregion. A highly drug-resistant P falciparum co-lineage is evolving, acquiring new resistance mechanisms, and spreading. Accelerated elimination of P falciparum malaria in this region is needed urgently, to prevent further spread and avoid a potential global health emergency. Funding: UK Department for International Development, Wellcome Trust, Bill & Melinda Gates Foundation, Medical Research Council, and National Institutes of Health.